Relation between sample size and deformation mechanism in Mg-Zn-Y 18R-LPSO single crystals. (December 2017) - Chuang, W.S.; Hsieh, C.H.; Huang, J.C.; Lin, P.H.; Takagi, K.; Mine, Y.; Takashima, K.
Abstract: With the long-period stacking ordered (LPSO) second phase, the promising mechanical properties of the Mg-Zn-Y alloys have been demonstrated. Because the LPSO phase plays an important role in strengthening mechanisms and it has the unique 18R crystal structure, it is interesting to clarify the deformation mechanism and size effect associated with this particular phase. In this study, uniaxial compression tests are conducted on LPSO along [11 2 ¯ 0] with different sample sizes. An apparent sample size effect is observed and the plastic deformation behavior of LPSO is found to change from kink to slip when sample size is reduced to a level about 1.8 μm in diameter. The non-basal prismatic slip system is found to operate within the smaller sized micro-pillars, different from the deformation kinking observed in larger sized samples. The probability of forming stair rod dislocations associated with the sample size effect is an important key to explain this change of plastic deformation behavior. It implies that the origin of deformation kink is non-basal prismatic slip. Graphical abstract: Highlights: The sample size effects in Mg-Zn-Y 18R-LPSO single crystals are examined. The deformation mechanisms in mini, micro, and nano scales are compared. The sample size effect is rationalized in terms of deformation mechanisms.